Green Fiscal Reforms : Part Two of Strengthening Inclusion and Facilitating the Green Transition - World Bank (Washington, DC, 2022)
In the post-pandemic world, EU member states will need to embrace two simultaneous challenges. These will include recovering from the COVID-19 pandemic and embracing the ambitions of the European Green Deal, which maps out broad policies aimed at achieving carbon neutrality by 2050 and reducing emissions by 55 percent by 2030. Compared to the emissions reduction achieved during 1990–2018 by the EU27 countries, the 2018–30 target is 50 percent more ambitious and is to be achieved in a third of the time. Meanwhile, the emissions reduction planned during 2030–50 will be even steeper. The transition in some EU countries will be particularly challenging, given their high energy intensity, significant dependence on fossil fuels for power generation and an increasing and environmentally unfriendly transport fleet. In addition, households will need to be supported in the transition, to avoid a substantial share of the population being adversely affected.